PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT DELAY DENGAN SUSTAINABILITY REPORTING SEBAGAI VARIABEL MODERASI - Anisa Nurvania Irmayunita; Stefanus Dimas Ryan Saputro (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to determine the effect of profitability and solvency on audit delay, with sustainability reporting as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The sample size for this study was 207. Secondary data were obtained from financial statements and termination reports. The analytical method used was multiple linear regression with descriptive statistical analysis, correlation analysis, r-square test, F-test, and t-test. It also included classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results showed that profitability had a negative and does not have a significant effect on audit delay, while solvency had a positive and significant effect on audit delay. The interaction of sustainability reporting with profitability and solvency does not have a significant effect on audit delay. However, sustainability reporting weakened the effect of solvency on audit delay. The implications of this study indicate that although sustainability reporting is expected to enhance transparency and audit efficiency, the findings do not provide significant support for this role. This suggests that sustainability reporting disclosures have not yet been optimally utilized as a corporate governance mechanism to accelerate the audit process.